The forgotten election administrator of internet voting: lessons from Estonia. (2nd November 2022) - Krivonosova, Iuliia
ABSTRACT: The introduction of new voting channels, voting technologies and other voting innovations are often thought to improve voter participation in elections and democracy. However, it frequently happens at the expense of administrators, who needs to deliver even more complex elections. This article traces how the introduction of a new voting channel, Internet voting, affects frontline administrators through a qualitative in-depth case study of the 2017 local elections in Estonia. Findings show that the local election administration plays a substantial role in delivering Internet voting, despite the centralized election hierarchy. The case shows little evidence to support the expectation that Internet voting decreases the administrative burden of local election officials. The article outlines the vulnerabilities in Internet voting administration, resulting from the complexity of delivering multi-channel elections, particularly the ones integrating Internet- and paper-based voting channels. The article makes important recommendations for improving the implementation of electronic voting and improving the quality of elections.